Evaluating the Food Profile in Qatar within the Energy–Water–Food Nexus Approach - Odi Fawwaz Alrebei (18288904) (2023)
Finding a balance between the capacity for production and the rising demand for food is the first step toward achieving food security. To achieve sustainable development on a national scale, decision-makers must use an energy, water, and food nexus approach that considers the relationships and interactions among these three resources as well as the synergies and trade-offs that result from the way they are handled. Therefore, this paper evaluates the Energy–Water–Food Nexus Profile of Qatar at a superstructural level by applying the Business-As-Usual (BAU) storyline; thus, trends of past data have been used to provide future projections to 2050 using the statistical prediction tools such as the compound annual growth rates of food demand (CAGRFD), international supply (CAGRFI), and the average local food supply change factor (c¯). Once the BAU storyline has been generated, the source-to-demand correlations have been defined for each food category. Such correlations include the annual and average ratios of the local food supply to the total demand (i.e., αi and α¯) and the ratios of the local food supply to the international supply (i.e., βi and β¯). In addition, as an effort to identify the required action to reach food self-sustainability, the additional local food supply to achieve (xi,add) and its ratio to the local demand (γ) have been defined. The highest average ratio of the local food supply to the total demand (αi) was found for the meat category, which was estimated to be 48.3%. Finally, to evaluate the feasibility of attaining food self-sustainability in Qatar, the water consumption (Vw,i) and its corresponding required energy for each food category have been estimated. Other Information Published in: Foods License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/foods12020230